Inhibitory effect of Monascus purpureus pigment extracts against fungi and mechanism of action - Majhi, Swapna; Dhale, Mohan Appasaheb; Honganoor Puttananjaiah, Mohankumari (Frontiers in Sustainable Food Systems, 2023)
The fungus Monascus produces several secondary metabolites of different pigment hues. These pigments have shown various biological activities. In this study, Monascus purpureus pigment extracts were tested (in vitro) against Penicillium expansum MTCC 4900, Rhizopus stolinfer MTCC 10595, and Aspergillus niger MTCC 8652 for antifungal activity. The UV–visible spectrum of M. purpureus fermented rice extracts showed λmax at 395, 425, and 500 nm. This indicated the solubility of yellow, orange, and red pigments in polar-based solvent extraction. The M. purpureus pigment extracts inhibited the radial growth and conidial germination of the test fungi. The fungi treated with pigment extract stained with DiBAC (a vital stain) emitted green fluorescence under a fluorescent microscope. These results indicated that the pigment extracts have affected the membrane potential of the treated fungi. Hence, the fungicidal activity of the pigment extracts is due to the disruption of the cell membrane. The HPLC analysis of the pigment revealed the presence of two major peaks. The UV–visible spectrum corresponding to the HPLC peak at 12-min retention time revealed the presence of orange pigment rubropunctatin. Apparently the rubropunctatin present in the extracts exhibited fungicidal activity. Further studies are warranted to assess the applications of M. purpureus pigments in preventing and treating fungus-related diseases.